THE ROLE OF THE GENERAL ELECTION SUPERVISORY AGENCY IN HANDLING VIOLATIONS IN THE 2024 OGAN ILIR REGIONAL HEAD ELECTION: PERAN BADAN PENGAWAS PEMILIHAN UMUM DALAM PENANGANAN PELANGGARAN PADA PEMILIHAN KEPALA DAERAH OGAN ILIR TAHUN 2024 - Puspa Indah Sari; Ridha Taqwa; Rudy Kurniawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Regional Head Elections (Pilkada) are the primary instrument for realizing popular sovereignty democratically. However, Pilkada practices are often tainted by administrative violations, violations of the organizer's code of ethics, and election crimes. This study aims to analyze the role of the Election Supervisory Agency (Bawaslu) of Ogan Ilir Regency in handling violations in the 2024 Pilkada. The research method used a qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the dominant violations in Ogan Ilir were administrative violations and violations of the organizer's code of ethics, while no vote buying practices were found. The violation reporting mechanism has been implemented, but there are still obstacles in the follow-up of Bawaslu recommendations by the General Elections Commission (KPU). This study emphasizes the need to strengthen Bawaslu's authority, increase human resource capacity, and encourage public participation in election supervision.